Note-Taking as a Technique in Teaching Reading Comprehension - Rusdiansyah Rusdiansyah (Institut Agama Islam Negeri Palopo, 2019)
The aim of this study is to explain the effective way in teaching reading comprehension through Note-Taking technique. Reading is an important skill in learning a language besides listening, speaking, and writing. It is an effort to increase our knowledge and achievement. Everyone should have the ability to read, especially in English because the fact shows that most of the scientific books are written in English. This research applied Classroom Action Research method by using four stages, such as; planning, implementation of action, observation, and reflection. This research conducted in two cycles. They were first and second cycle. Each cycle comprises the series of activities which relates each other. The realization of the second cycle was continued and improved based on the evaluation of the first cycle. The results of this research can be explained that note taking technique increase students’ reading comprehension. In this research, the researcher applied note-taking technique to increase students’ reading comprehension ability because by using note-taking technique the students are easier to make note and easy to answer the questions. They can explain about the keywords or the main ideas of the text, and absolutely they can comprehend the text. The result of the students is increasing by looking their score in cycle 1 and cycle 2. Their mean score in cycle 1 only 51 and cycle 2 the score develops to be 76. It means that the student’s reading comprehension was increased.